Cross-reacting herpes simplex virus antigens in hamster and mouse cells transformed by ultraviolet light-inactivated herpes simplex virus type 2. - Boyd, A L (1976)
Murine and hamster cell lines, each transformed with a different strain of herpes simplex virus (HSV), were examined for cross-reacting antigens by in vitro and in vivo assays. A comparative study by the indirect immunofluorescence technique detected common cross-reacting viral antigens. Cytoplasmic fluorescence patterns were observed in the 333-8-9 hamster line, the H238 murine line, and the H238 clonal lines; these patterns were identical to the fluorescence pattern of HSV -2-infected controls when reacted with HSV antiserum. Tumor rejection studies in the BALB/c host indicated that each cell line provided immunity against a tumorigenic challenge of transformed mouse cells. The H238 clone EC1 3 provided a 53% immunity against itself at an inoculum of 10(6); the 333-8-9 line supported a 26% immunity. These data demonstrate a common HSV antigenicity between the murine and hamster transformed lines and further indicate that the HSV genome is involved in transformation.